MODEL PEMBELAJARAN BERBASIS PORTOFOLIO PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Faridah, N. Ai St. Minhatul; Fitriani, Nia; Khadijah, Ifah; Aryani, Wiwik Dyah (Penerbit Widina, Widina Media Utama, 2025)
The portfolio-based learning model offers a student-centered authentic assessment approach, allowing educators to evaluate learning development holistically. This paper examines the implementation of portfolio-based learning models in the context of Islamic Religious Education (PAI) subjects in elementary schools, supported by theoretical foundations from constructivism, Ausubel's meaningful learning theory, and authentic assessment theory. Through systematic collection and reflection on students' work, portfolios serve as formative and summative tools that empower students to reflect on their Islamic learning, internalize Islamic values, and develop deep understanding. This paper discusses the theoretical relevance, practical implementation steps, benefits, and challenges and solutions in adopting this model to improve the quality of PAI learning at the primary level.ABSTRAKModel pembelajaran berbasis portofolio menawarkan pendekatan penilaian autentik yang berpusat pada siswa, memungkinkan pendidik untuk mengevaluasi perkembangan belajar secara holistik. Makalah ini mengkaji implementasi model pembelajaran berbasis portofolio dalam konteks mata pelajaran Pendidikan Agama Islam (PAI) di Sekolah Dasar, didukung oleh landasan teoritis dari konstruktivisme, teori belajar bermakna Ausubel, dan teori penilaian autentik. Melalui pengumpulan sistematis dan refleksi terhadap hasil karya siswa, portofolio berfungsi sebagai alat formatif dan sumatif yang memberdayakan siswa untuk merefleksikan pembelajaran PAI mereka, menginternalisasi nilai-nilai Islam, dan mengembangkan pemahaman yang mendalam. Makalah ini membahas relevansi teoritis, langkah-langkah implementasi praktis, manfaat, serta tantangan dan solusi dalam mengadopsi model ini untuk meningkatkan kualitas pembelajaran PAI di tingkat dasar.